Impact of Pandemic Measures on Emergency Department Visits: A Comparative Analysis of Medico-Legal Cases Before and During COVID-19 - Mehmet Berkay Can; Alper Özkök; Mehmet Ali Aslaner; Taner Akar; Birol Demirel (Gazi Medical Journal)
Objective: Proper analysis of the pandemic is vital for correctly managing future crises, predicting the problems encountered, reducing their effects, and taking appropriate precautions. In this study, we aimed to compare cases of emergency department (ED) in a tertiary care adult ED during the pandemic and the pre-pandemic periods to evaluate the effect of lockdowns and similar restrictive measures. Methods: “Pandemic period” was defined as the period between 11.03.2020 and 11.03.2021, and “pre-pandemic period” was defined as the period between the same dates in the previous year. Thousand cases (500 from each period) were selected by sampling method among 7137 medicolegal cases presented to the Adult ED in these two years. The total number of ED admissions and medico-legal cases’ quality, frequency, and diversity were compared. Results: Total admissions to the adult ED decreased by 42.8% during the pandemic period compared with the pre-pandemic period. Although medico-legal cases also decreased, their proportion in all admissions increased by more than 50%. Leaving the hospital voluntarily reduced significantly (p<0.001). There was a significant decrease in the daily average number of medico-legal cases during the full-day lockdowns of the pandemic compared with all other periods (p<0.001). Medico-legal cases decreased on weekends when the lockdown was imposed more frequently (p<0.046). In the pandemic, traffic accidents increased due to motorcycle accidents (p<0.010). Conclusion: During the pandemic, the significant decrease in overall ED visits compared with the number of medico-legal cases and the decline in the behavior of leaving the hospital voluntarily can indicate the high number of unnecessary green zone admissions in ordinary times. The change in living and consumption habits caused by the pandemic may also have changed the frequency and epidemiological distribution of forensic cases, such as motorcycle accidents.